2022
DOI: 10.1111/pde.15149
|View full text |Cite
|
Sign up to set email alerts
|

Development of an artificial intelligence algorithm for the diagnosis of infantile hemangiomas

Abstract: Prompt and accurate diagnosis of infantile hemangiomas is essential to prevent potential complications. This can be difficult due to high rates of misdiagnosis and poor access to pediatric dermatologists. In this study, we trained an artificial intelligence algorithm to diagnose infantile hemangiomas based on clinical images. Our algorithm achieved a 91.7% overall accuracy in the diagnosis of facial infantile hemangiomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…This algorithm demonstrated a diagnostic accuracy of 91.7% for facial hemangiomas in infants. [41] Cluster 8 primarily referred to computer vision systems and skin cancer dermatologists. Friedman RJ and colleagues conducted a blinded comparison study to evaluate the diagnostic performance of dermoscopic and automatic multispectral computer vision systems for detecting small, pigmented skin lesions.…”
Section: Research Hotspots and Future Directionsmentioning
confidence: 99%
“…This algorithm demonstrated a diagnostic accuracy of 91.7% for facial hemangiomas in infants. [41] Cluster 8 primarily referred to computer vision systems and skin cancer dermatologists. Friedman RJ and colleagues conducted a blinded comparison study to evaluate the diagnostic performance of dermoscopic and automatic multispectral computer vision systems for detecting small, pigmented skin lesions.…”
Section: Research Hotspots and Future Directionsmentioning
confidence: 99%
“…Tognetti et al [60] applied dermoscopic images to develop a DL-CNN model in the classification between atypical nevi from early melanomas, which achieved adequate accuracy (AUC: 90.3, sensitivity: 86.5%, and specificity: 73.6%) and eliminated the influence from dermatologists' experience. Several AI-based algorithms on novel resources also achieved accurate diagnostic performance for skin neoplasms including photos of skin neoplasms [61], umbilical cord blood sera [62], and electronic colorimeters [63].…”
Section: Extracranial Tumor Diagnosismentioning
confidence: 99%
“…Currently, the demand for pediatric dermatologists far exceeds the available workforce, with wait times for clinical visits surpassing all other pediatric specialties. 6,7 Patients often have to travel long distances to see a specialized provider. A study conducted in 2020 showed that 98% of all board-certified pediatric dermatologist practiced in metropolitan counties, 0% practiced in rural counties, and nine states had no pediatric dermatologist.…”
Section: Most Dermatology-related Ai Publications Involve Adult Datasetsmentioning
confidence: 99%
“…To overcome this disparity, AI‐based technology needs to be extended to pediatric patients. Currently, the demand for pediatric dermatologists far exceeds the available workforce, with wait times for clinical visits surpassing all other pediatric specialties 6,7 . Patients often have to travel long distances to see a specialized provider.…”
mentioning
confidence: 99%
See 1 more Smart Citation